Innate Immune Cells in Liver Inflammation. (9th August 2012) - Liaskou, Evaggelia; Wilson, Daisy V.; Oo, Ye H.
Abstract : Innate immune system is the first line of defence against invading pathogens that is critical for the overall survival of the host. Human liver is characterised by a dual blood supply, with 80% of blood entering through the portal vein carrying nutrients and bacterial endotoxin from the gastrointestinal tract. The liver is thus constantly exposed to antigenic loads. Therefore, pathogenic microorganism must be efficiently eliminated whilst harmless antigens derived from the gastrointestinal tract need to be tolerized in the liver. In order to achieve this, the liver innate immune system is equipped with multiple cellular components; monocytes, macrophages, granulocytes, natural killer cells, and dendritic cells which coordinate to exert tolerogenic environment at the same time detect, respond, and eliminate invading pathogens, infected or transformed self to mount immunity. This paper will discuss the innate immune cells that take part in human liver inflammation, and their roles in both resolution of inflammation and tissue repair.